Expect the Unexpected Enrichment of “Hidden Proteome” of Seeds and Tubers by Depletion of Storage Proteins - Gupta, Ravi; Min, Cheol W.; Wang, Yiming; Kim, Yong C.; Agrawal, Ganesh K.; Rakwal, Randeep; Kim, Sun T. (Frontiers in Plant Science, 2016)
Dynamic resolution of seed and tuber protein samples is highly limited due to the presence of high-abundance storage proteins (SPs). These proteins inevitably obscure the low-abundance proteins (LAPs) impeding their identification and characterization. To facilitate the detection of LAPs, several methods have been developed during the past decade, enriching the proteome with extreme proteins. Most of these methods, if not all, are based on the specific removal of SPs which ultimately magnify the proteome coverage. In this mini-review, we summarize the available methods that have been developed over the years for the enrichment of LAPs either from seeds or tubers. Incorporation of these methods during the protein extraction step will be helpful in understanding the seed/tuber biology in greater detail.